Calibration of a stress-strain response for geopolymer concrete under axial compressive load - Dong, Van Dao (Institution of Mechanical Engineers, 2022)
The use of geopolymer concrete (GPC) in common load-bearing structures is still limited, mainly due to the lack of specific design procedures and limited understanding of the stress–strain behavior under uniaxial loading. The present work investigates the mechanical responses of GPC under axial compressive load by conducting a large number of experiments. For this purpose, 198 samples with three GPC mixes were designed, including concrete grades of 30, 40, and 50 MPa. The samples were prepared following the ASTM standards to determine the stress–strain relationship under compression. The results showed that fly ash-based GPC had average elastic modulus values of 30.424, 31.497, and 33.650 GPa, respectively, for G30, G40, and G50, lower than estimated using formulae for Ordinary Portland Cement (OPC) concrete, such as ACI standard 318-11, AASHTO-2007, and others. Furthermore, a novel model of GPC stress–strain response was proposed, mainly based on the empirical formulation suggested by Sargin using a modified factor D. Besides, the deformation of GPC was observed larger than that of OPC with similar strength, for instance, the strain at peak stress εc=2.45−2.75‰. The GPC was also found to have better plasticity behavior than OPC while conducting the axial stress–strain response, with the obtained values of εcu=3.2−4‰. The findings of this work might lead to additional in-depth research into GPC's mechanical characteristics, particularly its structural behavior